نمذجة مشكلة التخطيط الإجمالي للإنتاج في حالة الطلب والتكاليف مبهمة - دراسة نظرية وتطبيقية - مكيديش, محمد; ساهد, عبد القادر (جامعة الوادي University of Eloued, 2015)
قمنا في هذا البحث بنمذجة مشكلة التخطيط الإجمالي للإنتاج في المؤسسة الوطنية للصناعات المعدنية غير الحديدية والمواد النافعة، وهذا حتى تتمكن إدارتها الإنتاجية من تحديد خطة إنتاج مثالية تواجه بها تقلبات الطلب الموسمية على منتجاتها ومن أجل ذلك استخدمنا نموذج البرمجة الرياضية المبهمة Fuzzy mathematical programming، في حالة الطلب والتكاليف مبهمة نظرا للظروف الغير مؤكدة التي تحيط بهما حيث قمنا بصياغة نموذج تقوم على إثره المؤسسة بتدنية هدف المؤسسة المتعلق بتدنية مجموع تكاليف الإنتاج والعمالة والتخزين وهذا باستخدام طريقة Chanas (1983)، ليتم في الأخير حل النموذج الرياضي باستخدام البرنامجين MATLAB و LINGO والحصول على خطة إنتاج مثلى In this study, we have modeling the problem of aggregate production planning(APP) in the national firm of iron manufactures non- metallic and useful substances so that its productive management can be able to specify an optimal production plan through which it faces the seasonal demand fluctuations on its products. For this, we have made use of Fuzzy mathematical programming In the case of fuzzy demand and fuzzy costs because of the circumstances surrounding uncertainty, where we have formulated a mathematical model is designed to minimize the total cost of production, workers, and storage, using for that the method of Chanas (1983), the mathematical model is solved by using MATLAB and LINGO programs and getting optimal production plan
Modeling of aggregate production planning problem in the case of fuzzy demand and fuzzy costs: Theory and Applied Study
مقال- مجلة رؤى اقتصادية
Keywords: التخطيط الإجمالي للإنتاج، البرمجة المبهمة، الطلب المبهم، التكاليف المبهمة، دوال الانتماء; Aggregate production planning , fuzzy programming , Fuzzy demand, fuzzy costs, Membership functions